前言：爲什麽應該重視公共健康倫理學的研究？: Introduction: Why Should We Prioritize Research in Public Health Ethics? - FAN, Ruiping; XU, Hanhui (International Journal of Chinese & Comparative Philosophy of Medicine, 2024)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. Public health is widely recognised as a public or collective good with non-rivalrous and non-exclusive traits. Nonetheless, the advancement of public health often demands resource allocation necessitating adherence to ethical standards in governmental policy and administrative practices. The diverse ethical principles of different cultures lead to diverse conceptualisations and implementations of effective policies to enhance public well-being. Hence, comparative cross-cultural analyses can offer valuable insights into pertinent matters. This collection of thematic essays and commentaries within the journal introduces and investigates key topics in research on public health ethics.